Severe First Trimester Recurrent Intrahepatic Cholestasis of Pregnancy: A Case Report and Literature Review - Hubschmann, Andrea G.; Orzechowski, Kelly M.; Berghella, Vincenzo (American Journal of Perinatology Reports, 2016)
Background Intrahepatic cholestasis of pregnancy (ICP) is a disorder of defective bile acid transport that results in systemic accumulation of bile acids and typically presents in the third trimester of pregnancy with intense pruritus. A positive linear correlation exists between total bile acid level and poor pregnancy outcome, and labor is typically induced at 37 weeks gestation to prevent intrauterine fetal demise (IUFD).Case Study We present the most severe reported case of recurrent ICP presenting early in the first trimester. The patient was delivered by repeat cesarean section at 31 6/7 weeks gestation resulting in a viable female infant.Conclusion Iatrogenic preterm delivery may be indicated in early-severe recurrent ICP to prevent IUFD, but more research is needed.
Keywords: severe recurrent ICP; first trimester; intrauterine fetal demise; preterm birth